Role of Stakeholders in Heritage Management in Bangladesh: A Case Study of Mahasthangarh - Khan, Mohammad Mahmudul Hasan (CenRaPS Journal of Social Sciences, 2020)
The notion of stakeholders is becoming increasingly significant in heritage management activities and planning. It is commonly argued that individuals, groups, organizations, environs, societies, institutions, and even the natural environment can be potential stakeholders. However, most of the case heritage sites are impacted and concerned by particular stakeholders such as the local community, regional government, and NGOs. Every project has stakeholders who can influence or be influenced by the project in a positive or negative manner. Mahasthangarh and its environs are a potential heritage site of South Asia that helps understand the chronological history and cultural development of Bengal Civilization. Like many other heritage sites in Bangladesh, Mahasthangarh faces serious threats and challenges which are damaging and waning its outstanding universal value of tangible and intangible heritage. Since site managers involve potential key stakeholders to enhance the sustainable heritage management, planning, reduce the possibility of conflict, increase the stakeholders’ ownership through regular communication, raising awareness, educational activities, and building campaigns, and to augment the community’s trust in heritage management; without the effective role of stakeholders, the outcomes are precarious and can be catastrophic. The paper will demonstrate the possibilities of using the roles of stakeholders as potential tools for safeguarding and managing the heritage site by using Mahasthangarh and its environs as a case study.